Optimization of wireless power transmission - Lim, Chen Loong (2018)
In this final year project, wireless power transmission (WPT) system is investigated. A WPT system is normally made up of one transmitter and one receiver. This type of conventional WPT system will be referred as CWPT system. In this project, however, parasitic element is inserted into the system. The WPT system integrated with parasitic element will be referred as PWPT system. There are different methods of inserting parasitic element into WPT system such as different shape, line up, and number. The first idea of PWPT system is created by using a parasitic wire in square shape, rectangular shape, straight lines, and rectangular shape with straight lines. After that, PWPT system is designed by locating parasitic element to different location, such as in front of transmitter or behind of transmitter. The last method is increasing the number of same shape and parameters of the parasitic element from one to maximum eight. In order to apply all the designs above, FEKO software is used as a platform to conduct the simulation. Method of Moment (MOM) is used by this software to solve the sophisticated mathematical electromagnetism problem. A series of steps are included to obtain the simulation result in FEKO, for example, modelling, declaring variables, meshing and simulating. The result obtained shows the power transfer efficiency (PTE) of a particular PWPT/CWPT system. In this research, the highest PTE obtained among all the model is PWPT system with eight parasitic rectangular wire which are located in front of vii receiver, in front of transmitter, beside of transmitter and behind of transmitter, all the four directions. However, the design of this PWPT system occupies lot of space which become the disadvantage if utilized it in the real life. A more compact and complex version of PWPT system hope can be designed meanwhile which can either maintain or increase the PTE of the system.